Penambahan Suplemen Herbal Temulawak (Curcuma zanthorrhiza) Pada Pakan Terhadap Gambaran Darah dan Tingkat Kelulushidupan (Survival rate) Ikan Lele Dumbo (Clarias gariepinus): indonesia - imas, imas rofi'ah; Barades, Epro; Rakhmawati, Rakhmawati (Jurnal Perikanan Terapan, 2022)
This final project will be carried out from July to August 2022 Teaching Farm Polytechnic State Polytechnic Lampung for 20 days starting from July to August 2022. This implementation aims to determine the total erythrocytes, leukocytes, and differential leukocytes and the survival of catfish fed with addition of temulawak herbal supplements to the immunity of catfish (clarias gariepinus). Maintenance use round tarpaulin pond with a diameter of 2 m with a stocking of 471 fish/m3 with two treatments namely K (without giving temulawak herbal supplement in feed) and A (supplementation of temulawak herb in feed). that seedThe size used is 5-9 cm. Maintenance is carried out for 20 days. From the results of maintenance on fish with treat the method of adding temulawak herbal supplements to feed, namely the survival rate of 98%, increase the good immune response in the body of the fish, the amount of feed consumption and growth performance, the average valueerythrocytes 2.83 × 106 cells/mm3, leukocytes 48.70 × 103 cells/mm3, lymphocytes 71.71%, neutrophils 16.42%, monocytes 6.14%, platelets116 × 103 cells/mm3 .